2014
DOI: 10.1021/jp500263h
|View full text |Cite
|
Sign up to set email alerts
|

Nonchromophoric Organic Matter Suppresses Polycyclic Aromatic Hydrocarbon Photolysis in Ice and at Ice Surfaces

Abstract: We have investigated the effects of organic matter (OM) that does not absorb sunlight ("nonchromophoric") on the reactive environment presented by bulk ice and ice surfaces. Fluorescence spectroscopy showed that the presence of as little as 2.5 × 10(-4) M octanol or decanol reduces the extent to which naphthalene self-associates at ice surfaces, which indicates that naphthalene partitions between ice and organic phases present there. We also measured photolysis kinetics of the polycyclic aromatic hydrocarbons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 36 publications
(82 reference statements)
6
46
2
Order By: Relevance
“…Table 1 shows first order anthracene photodegradation rate constants in aqueous solution and artificial snow. In agreement with several previous studies, 13,17,36,37 though in contrast to Ref. 10, we measure a larger rate constant in the frozen sample.…”
Section: Photodegradation Kineticssupporting
confidence: 93%
See 1 more Smart Citation
“…Table 1 shows first order anthracene photodegradation rate constants in aqueous solution and artificial snow. In agreement with several previous studies, 13,17,36,37 though in contrast to Ref. 10, we measure a larger rate constant in the frozen sample.…”
Section: Photodegradation Kineticssupporting
confidence: 93%
“…We have reported that anthracene photodegradation rate constants at frozen decanol surfaces are below the detection limit of 5 × 10 -5 s -1 , at least a factor of 10 smaller than rate constants in ice granules prepared from DI water. 37 Several factors may contribute to the faster photodegradation in frozen NaCl solutions. Chemical fate models often assume that reactions in snow and ice occur within liquid volumes formed by brine formation during freezing.…”
Section: Photodegradation Kineticsmentioning
confidence: 99%
“…This effect has recently been demonstrated in the laboratory, where the photolysis kinetics of anthracene, pyrene, and phenanthrene in ice samples were slowed substantially in the presence of trace amounts of nonchromophoric organics. 265 …”
Section: Heterogeneous Photochemistry At Ice Surfacesmentioning
confidence: 99%
“…Many physical and chemical processes occur very differently at liquid and frozen water surfaces. For example, a number of aromatic pollutants have been reported to photolyze more rapidly at ice surfaces than at liquid water surfaces, and some aromatic pollutants that do not photolyze in aqueous solution can photolyze at ice surfaces. Heterogeneous reaction kinetics have also been reported to differ at frozen and liquid water surfaces: ozonation of several aromatic species has been reported to be much faster at ice surfaces than at liquid water surfaces, while hydroxyl radicals (OH), which react rapidly with aromatic species at liquid water surfaces, have been reported to be unreactive toward a range of aromatic species at ice surfaces. , If solutes cause the surface to be coated in a liquid “brine”, then these physical and chemical processes will occur as though the surface is a liquid rather than a solid and can be modeled as such. There is some evidence that this might be the case: the photolysis rate constant of the aromatic dye harmine was larger at frozen freshwater surfaces than in aqueous solution, but no enhancement compared to in aqueous solution was observed at the surface of frozen NaCl solutions when initial NaCl concentrations exceeded 0.2 M. These results were interpreted as indicating that the reaction environment experienced by harmine transitioned from that of an ice surface to a liquid brine as the NaCl concentration increased …”
Section: Introductionmentioning
confidence: 99%